Nilai-Nilai Pendidikan Islam Dalam Tradisi Sunatan Pada Masyarakat Bumiayu - Novan Ardy Wiyani (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: The tradition of circumcision in Bumiayu did not arise by itself. Appearance is the result of understanding and interpretation of the hadith about prayer working order for 10-year-old child. In the tradition of circumcision, there are seven series of activities, ranging from nggasrep, kungkum nang kali, nggelar klasa, sunatan, terbangan, ngrayah duit, and walimahan. The seventh series of activities each has different objectives that various Islamic educational value in it. Keywords : tradition, circumcision, education, Islam.